Common source theory and composition Of the story of the divided monarchy in kings With special emphasis on the account of Josiah's reform - Kucová, Lydie (The University of Edinburgh, 2005)
This thesis seeks to contribute to a dynamic scholarly debate regarding the relationship of the biblical books of Samuel-Kings and Chronicles. The wider frame of reference, in which this study is set, is on the one hand, the prevailing view since de Wette that the main source of Chronicles is Samuel-Kings by and large in its existing form, and on the other, the recently revived older theory of a common source behind both Samuel-Kings and Chronicles. The present investigation looks at the merits of the latter, particularly the challenge it poses to the view of Chronicles being dependent on Samuel-Kings, as the portions of Kings and Chronicles dealing with divided monarchy in general and the reform of Josiah in particular are considered

After preliminary matters in the introduction, the regnal framework and the royal cultic reforms as presented in Kings and Chronicles are examined in chapters one and two. One of the major conclusions drawn from text and literary critical studies of the regnal formulae of these two historiographical works is that the framework of Israelite rulers in Kings may be a later (=postchronistic) development in that book, since close links are observed between the parts of regnal formulae of Judean monarchs in Kings that are absent from Chronicles and the framework of the rulers of Israel included only in Kings. The cultic reform accounts in Kings display a set of common characteristics often considered 'deuteronomistic'. Since these language characteristics are also shared by the reform narratives in Chronicles, it is argued that, in this sense, Chronicles in its reform accounts is no less 'deuteronomistic' than Kings. Of the only two cultic reform narratives that are found in Kings but not in Chronicles, the one relating to Jehu includes a subtle link to the ElijahElisha cycle that occurs again only in Kings, thus implying that both Jehu's reform account and the Elijah-Elisha cycle with which it is closely connected were originally absent from the main source of Chronicles. A major investigation is launched in chapter three into the parallel texts of one of the more prominent shared cultic reform accounts, that of king Josiah (2Kgs 23:4-20 + 24 and 2Chr 33:4-7 + 33). The study culminates with a tentative proposal of a primary form of Josiah's reform report that lies behind the two parallel texts. The next chapter investigates how that earlier reform account was expanded in Kings, as well as the many connections with other texts both within and outside the book of Kings in the process of its evolution. With the findings of the study of the texts of Josiah's reform in Kings and Chronicles in the major part of the thesis endorsing the main tenets of common source theory, the final chapter then hints at similar processes for other parts of Kings relating to the story of the divided monarchy, where the texts may have developed from the shorter material identifiable also as the main source for Chronicles.